Effect of logging on timaliidae diversity and abundance in Berkelah Forest Reserve, Pahang, Malaysia - Mohd Fauzi, Nor Azlin (2018)
The composition, structure, and density of bird community of Berkelah Forest Reserve, Maran, Pahang, Malaysia were investigated in selective logged forest and compared with those in primary forest of the same forest reserve. Distance sampling transect count and mist netting methods were carried out in 30, 388.65 ha located at latitude (3.767 degrees) 3° 46' 1" North of the Equator and longitude (103.017 degrees) 103° 1' 1" East. The main objective of this study was to investigate how logging activities affect the species richness, community composition, and microclimate and microhabitat-use pattern of the Timaliidae mainly in forest reserve for future management and conservation efforts. Timaliidae family was selected as the focal family for the study, due to its occurrence in tropical rainforest. Large number of the Timaliidae are specialist, which makes some of the selected species suitable to be used as indicator species for forest ecosystem health. A total of 39,168 individuals were recorded from September 2009 until April 2011. Thus, this showed that the population of birds in the Berkelah Forest Reserve was high. Out of 164 species which have been found in the study area, a total of 20 species (12%) were from Timaliidae’s family. All of the 20 species of Timaliidae were found in primary and 19 species of Timaliidae were found in logged areas. Among the 20 species, the Black-throated Babbler Stachyris nigricollis was found absent in logged forest. The Horsfield’s Babbler Malacocincla sepiarium (593 individuals) and Short tailed Babbler Malacocincla malaccensis (574 individuals) were found in high number in both primary and logged forest of Berkelah Forest Reserve. The location of the forest itself is an advantage because it is closely located and partly linked to other forest reserves while also being near to national parks in Pahang. The study had found that based from the transect count data, density species in primary forest was 6.62 ± 0.41 birds/ha with total number of observations of 2905. The estimated number of individuals in the primary forest is N=1457 ± 90.795 calculated at 95% of confidence interval. Whereas, the result for logged forest was observation 1525 with the density of 2.7069 ± 0.2317 birds/ha. The number of estimated individuals was N = 433.00 ± 37.062 with 95% confidence interval. The result indicated a significant different between density in logged and primary forest with p < 0.5. The second objective was to determine the microhabitat and microclimate factors that affect the population size of Timaliidae in primary and logged forest. In this study, the habitat preference was determined by looking at the number of species in the study area of study. The parameters which were tested in the study involved microclimate particularly forest temperature, humidity, soil temperature and lux intensity. Whereas for microhabitat, plant dbh, shrubs, canopy cover and elevation were also measured. Most of the Timaliidae species were strongly associated to trees with dbh of 30 cm–50 cm and above as well as shrubs. Based on the canonical correspondence analysis, General Linear Model Statistic (GLMS) and regression analysis, it was found that there were three (3) parameters that are significantly and strongly associated with the presence of bird species based on their preference namely understorey temperature, soil temperature and humidity. The last objective was to determine the most suitable Timaliidae species to be used as indicator species of forest ecosystem health. Based on the results, five species of Timaliidae species were selected as biological indicator for forest ecosystem health. The study suggested that Black-capped Babbler Pellorneum capistratum, Short-tailed Babbler Malacocincla malaccencis, Black-throated Babbler Stachyris nigricollis, Ferruginous Babbler Thrichostoma bicolor, and White Bellied Yuhina Yuhina zantholeuca are fit and suitable to be used as forest ecosystem health indicators. The finding of this study indicated that, the main factors affecting the species abundance and distribution can be used by relevant agencies in wildlife and habitat management strategies.